Zearalenone and deoxynivalenol reduced Th1-mediated cellular immune response after Listeria monocytogenes infection by inhibiting CD4+ T cell activation and differentiation. (1st September 2021) - Cai, Guodong; Xia, Sugan; Zhong, Fang; Liu, Shuangshuang; Gu, Jianhong; Yuan, Yan; Zhu, Guoqiang; Zou, Hui; Liu, Zongping; Bian, Jianchun
Abstract: Based on the fact that mycotoxins and the food-borne bacteria coexist in the natural environment and pose a significant health hazard to humans and animals, it is important to investigate the immunosuppressive mechanism of ZEA (zearalenone), DON (deoxynivalenol), and their combination in bacterial infections. In this study, we established a mouse model of mycotoxin low-dose exposure combined with Listeria monocytogenes infection and investigated the effects of ZEA, DON and their combination on Th1-mediated anti-intracellular bacterial infection based on CD4 + T cell activation and differentiation using both in vitro and in vivo analyses. The present study showed that both ZEA and DON aggravated Listeria monocytogenes infection in mice and affected the activation of CD4 + T cells and Th1 differentiation, including the effects on costimulatory molecules CD28 and CD152 and on cross-linking of IL-12 and IL-12R, by inhibiting T cell receptor (TCR) signaling. When compared with ZEA, DON was found to have a greater impact on many related indicators. Surprisingly, the combined effects of ZEA and DON did not appear to enhance toxicity compared to treatment with the individual mycotoxins. Our findings more clearly revealed that exposure to low-dose ZEA and DON caused immunosuppression in the body by mechanisms including inhibition of CD4 + T cells activation and reduction of Th1 cell differentiation, thus exacerbating infection of animals by Listeria monocytogenes . Graphical abstract: Image 1 Highlights: ZEA, DON aggravated Listeria monocytogenes infection in mice. ZEA, DON inhibited the activation of naive CD4 + T cells in vitro and in vivo. ZEA, DON inhibited the differentiation of naive CD4 + T cells into Th1 subtype. The key cause of these negative effects of ZEA, DON is reduced TCR signaling.